A Review of Selected Hydrology Topics to Support Bank Operations - World Bank (Washington, DC, 2013)
The World Bank's 2004 Water Resources Sector Strategy focused on the need for both water resources management and development in dealing with growth and poverty alleviation. Planning and design of new hydraulic infrastructure for water supply and sanitation, food production, hydropower generation, flood protection, ecosystem restoration or other such purposes require dealing with all elements in the interaction among land, water, vegetation, human intervention and climate variability and change, with an emphasis on the end-user. They also require the simultaneous consideration of technical, economic, institutional (governance), political, financial, environmental and social factors, as called for in the Bank s 1993 Water Resources Management Policy. To provide high-level insight on the key hydrology issues involved, a group of world class experts gathered at a workshop held at World Bank Headquarters in November 2008. The workshop was organized by the Hydrology Expert Facility (HEF) of the Water Anchor. The presenters discussed advancements in key hydrologic topics that were selected for their relevance to Bank operations. The focus was on potential implications for the Bank s development assistance on water projects, programs and policies.